Personnel Administration Burden at the Semarang Regency Public Works Office - Ishaq Dhimas Bayuaji; Nathaniel, Timothy (Arkus, 2024)
Administrative expenses are all forms of activities that are supporting and do not directly contribute to achieving organizational goals. This study aims to describe the administrative burden on the Semarang Regency Public Works Office, one of the regional apparatus organizations (OPD) responsible for providing public works infrastructure in the area. This study analyzes the administrative burden in terms of finance, human resources and work processes. The results of the analysis show that the administrative burden from a financial perspective is still low, while the administrative burden in terms of human resources and work processes is quite high. There are several efforts to optimize administrative management, such as increasing employee capacity and competence, utilizing information technology, simplifying procedures, increasing transparency and accountability, and carrying out regular monitoring and evaluation. The aim of this effort is to reduce the administrative burden to a minimum, so as to increase the efficiency and effectiveness of OPD in carrying out public works affairs in Semarang Regency.